2018
DOI: 10.33495/jacr_v8i7.20.138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of marketing intermediaries on pricing of agricultural perishable products: A case study of onions and tomatoes in Benue State, Nigeria

Abstract: The study examined the effect of marketing intermediaries on pricing of agricultural perishable products in Benue State, Nigeria. Multistage sampling technique was employed to select 300 tomato and onion marketers in the study area. Primary data were collected using well-structured questionnaire administered on respondents. Data collected were analyzed using descriptive statistics, pricing efficiency and gross margin. The study revealed that majority (57.3%) of the respondents were female, 49.3% were married w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…The previous research was analyzing the efficiency of marketing prices of horticultural crops especially for shallots and found that there were inefficient marketing channels (A. et al, 2018;Adegbite & Adejobi, 2018;Dukpa, 2020;Mentafa et al, 2017;Ocholi et al, 2021). Hence, the researchers are interested in examining this issue to prove whether shallot marketing in the research area in Malang Raya is efficient or not.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research was analyzing the efficiency of marketing prices of horticultural crops especially for shallots and found that there were inefficient marketing channels (A. et al, 2018;Adegbite & Adejobi, 2018;Dukpa, 2020;Mentafa et al, 2017;Ocholi et al, 2021). Hence, the researchers are interested in examining this issue to prove whether shallot marketing in the research area in Malang Raya is efficient or not.…”
Section: Introductionmentioning
confidence: 99%